Guillain-Barré syndrome: a rare association of COVID-19 pneumonia at presentation - Mahur, Hemant; Mathur, Kartikeya; Singh, D. P.; Chahar, Umesh; S., Darshan R.; S., Shivakanth M. (International Journal of Research in Medical Sciences, 2021)
COVID-19 is a global pandemic which has varied array of symptoms. A neurotropic presentation has also been described of which the most common is stroke. In this brief communication we report a case of COVID-19 who presented to our hospital with features suggestive of Guillain-Barré syndrome. A 76 year old male presented with chief complains of weakness in both lower limbs. On detailed examination the patient had LMN type quadriparesis without sensory involvement. Diagnosis of GBS was confirmed by CSF and NCV studies and other cases of quadriparesis were ruled out by appropriate investigations and treatment of the same was started. Respiratory examination revealed bilateral basal crepitations and CXR revealed B/L lower zone haziness so a secondary diagnosis of B/L Atypical Pneumonitis suspected COVID-19 was kept. A COVID-19 RTPCR turned out to be negative initially. However, looking at respiratory signs and symptoms along with increase in inflammatory markers a repeat COVID RTPCR was planned which turned out to be positive. Patient was further managed on the line of COVID-19 pneumonitis. He responded well to the treatment and is now asymptomatic on follow up. Nervous system involvement in COVID-19 may have been grossly underestimated. Over the course of this pandemic, an increasing number of COVID-19 patients are being reported with neurological complications. Physicians should be aware of atypical presentation where patient complained of weakness first and had respiratory symptoms later as in our case where early detection of atypical presentations help in better management.